Penentuan Strategi Pemasaran Tote Bag Lurik (BAGRIK) : Analisis SWOT - Rini Setyowati; Siti Fatimah Nurhayati (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Tote Bag Lurik (BAGRIK) is a tote bag product and its derivatives made from lurik patchwork. The use of lurik patchwork is a form of regional cultural preservation and waste utilization efforts in creating and developing innovative and creative potential products. The products produced from the management of lurik patchwork are so diverse that marketing efforts are not easy. The marketing process is one of the important parts that must be considered, in the marketing process determining the right strategy must be done so that the company is able to maintain and develop its business. SWOT analysis is used as a form of effort in identifying existing problems so that the company's goals can achieve the expected targets. Limitations in promotional facilities and the lack of public interest in products made from lurik are weaknesses for BAGRIK. The large number of competitors and price competition between producers is a threat to BAGRIK. So that a marketing strategy can be found that can be applied in an effort to maintain its business by always maintaining and improving product quality, not lowering the standards of the products produced, establishing good interactions with consumers, making good use of technological developments, increasing public interest in products made from lurik by conducting more education about lurik and the products produced.